Evaluating malocclusion patterns in children with autism spectrum disorder using the index of complexity, outcome and need: a cross-sectional study - Fahimeh Farzanegan; Sahar Ahmadi Shadmehri; Zahra Shooshtari; Amir Reza Hamidi; Arsalan Shahri (BMC, 2024)
Abstract Background The purpose of this study was to evaluate the complexity of malocclusion and existing patterns in children with autism spectrum disorders (ASD) using the index of complexity, outcome and need (ICON). Methods This cross-sectional study included children diagnosed with ASD, aged 9-15 years. A group of healthy children with the same demographic characteristics was randomly selected as the control group. Malocclusion was assessed according to ICON scoring protocol. The following parameters were recorded: dental aesthetics, upper arch crowding/spacing, presence of crossbite, anterior-vertical relationship (open and deep bite) and buccal segment anterior-posterior relationship. Finally, an overall ICON score was derived and reported for each patient. Descriptive analysis was performed for all investigated variables. Significance level was set at p < 0.05. Results A total of 324 children, divided into ASD (162) and control (162) groups, comprised the study population. Our results demonstrated that the average overall ICON score was significantly higher in the ASD group compared to the control group (38.77 vs. 27.43, p < 0.001). ASD children also obtained significantly higher scores regarding the dental aesthetics component (3.84 vs 2.78, p < 0.001). Study groups were significantly different in terms of the prevalence of incisor overbite and open bite (p = 0.002 and p < 0.001, respectively). Patients in the ASD group showed a higher prevalence of Class II and Class III malocclusions (p < 0.001). Conclusion ASD children obtained significantly higher overall ICON scores, indicating more complex and severe malocclusions. These children also exhibited a greater tendency towards Class II and III malocclusions.